Hip arthroplasty in Montenegro: satisfaction and experience of hip arthroplasty patients with health care in correlation with comorbidity - Magdelinic, Gordana; Magdalenic, Milan; Knezevic, Mirka; Magdalenic, Milena; Mijuskovic, Ana (Medicinski časopis, 2024)
Introduction/Objective: The goal of this research was to determine the importance of hip arthroplasty in Montenegro through patient satisfaction and experience with health care, as well as the impact of comorbidities on the recovery and general health of patients after surgery.Methods: This retrospective study was conducted among 184 patients who underwent hip replacement in Montenegro, at the Clinical Center of Montenegro and General Hospital Berane. We collected data during October 2019 to February 2020 at outpatient control visits, where respondents voluntarily filled out the questionnaire.Resuls: Based on the responses received after the survey, a high level of patient satisfaction with health care was established. The average score of hip pain before surgery in the subjects was 4.35 ± 0.86, and after the surgery there was a statistically significant improvement (t = 23.517; p=0.001), and the average score was 2.46 ± 0.86. Hip-related difficulties were rated as 4.61 ± 0.92 before surgery and 3.09 ± 0.95 after surgery. Using the ANOVA test, a statistically significant difference was found in the quality of mental and general health of subjects with hip surgery in terms of comorbidity present (p < 0.05).  Conslusion: The research results indicated that greater satisfaction with the health care of patients with hip arthroplasty predicts a better quality of recovery. Respondents with metabolic and digestive diseases and respondents with cardiovascular diseases rated the quality of general and mental health the worst after surgery.
Keywords: hip arthroplasty; satisfaction; health care; comorbidity